The influence of promotion mix on enhancement of student enrolment in UniKL MIMET/ Amirah Ramlan - Ramlan, Amirah (2018)
The study objective is to identify the influence of promotion mix on enhancement of student enrolment in UniKL MIMET. The variables are student enrolment, advertising, direct marketing and personal selling. To attain the objectives of this research, there has three hypothesis are developed and tested. Besides that, each hypothesis were measured and the results obtained are subsequently explained. Literature reviews was included in this research project as to provide better understanding on the influence of promotion mix and also provide justification on the research questions and research problems. The study used the descriptive research design and used questionnaires as data collection instruments. Then, the respondent was a bachelor's student at UniKL MIMET and 125 respondents was selected using stratified sampling techniques. The data were analyses by Scientific Programme for Social Sciences (SPSS 20.0). After that, the analysis was presented by using figures and tables and the analysis concludes that direct marketing has a significantly influence with student enrolment in UniKL MIMET thus it means that direct marketing has influence on student enrolment.